SUSTAINABLE DEVELOPMENT GOAL FOUR (SDG4): CHALLENGES AND THE WAY FORWARD - Ossai, A.G (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Education has been variously recognized not only as a fundamental human rights but also as a veritable instrument for sustainable development and equally as a vehicle for confronting the challenges facing the society. Equally, sustainable development Goal four (SDG4) has been identified as constituting a force to social and economic development of a nation. Sustainable Development Goal Four is a major driver in the achievement of all the SDGs in Nigeria. As a matter of fact, Nigeria as a member of the united Nations, is committed to the achievement of not only the human rights enshrined in the Universal declarations of Human right of 1948 but also the Global Goals, especially Sustainable Development Goal Four, tagged inclusive education, this paper analyzes the concept of sustainable development, examines the United Nations Educational, Scientific and Cultural Organization (UNESCO) sustainable Development Goals four and its conceptual dimensions. It also highlighted the challenges facing the achievement of Sustainable Development Goal Four in Nigeria and suggested some of the way forward, these include amongst others, provision of conducive environment for learning, reorganization of the curriculum of learning, effective communication, proper teaching methods e.t.c. The paper concluded that Nigeria is still in a long way to achieving this sustainable Development Goal Four.